Polysomnographically Defined Restless Sleep Disorder and Periodic Limb Movements during Sleep in Children Born Prematurely - Lourdes M. DelRosso; Hovig Artinian; Maria P. Mogavero; Oliviero Bruni; Manisha Witmans; Mary Anne Tablizo; Michelle Sobremonte-King; Raffaele Ferri (MDPI AG, 2024)
Introduction: Children born prematurely (<37 weeks' gestation) are at increased risk of perinatal complications, comorbidities, and iron deficiency. Iron deficiency is associated with restless legs syndrome and periodic limb movement disorder. In this study, we assessed the prevalence of restless sleep disorder (RSD) and elevated periodic limb movements during sleep (PLMS) in children born prematurely who underwent polysomnography. Methods: A retrospective chart review of sleep studies was conducted in children aged 1-18 years (median age 4 years) with a history of premature birth. Children with genetic syndrome, airway surgery, or tracheostomy were excluded. Three groups were compared: children with PLMS index >5, children with RSD, and children with neither elevated PLMS index nor RSD. Results: During the study, 2577 sleep studies were reviewed. Ninety-two studies fit our criteria and were included in the analysis. The median age at birth was 31 weeks, and the interquartile range (IQR) was 27-34 weeks. A total of 32 (34.8%) children were referred for restless sleep and 55 (59.8%) for snoring. After polysomnography, 18% were found to have a PLMS index >5/h, and 14% fit the criteria for restless sleep disorder (RSD). There were no statistically significant differences in PSG parameters among the children with RSD, PLMS, and the remaining group, except for lower obstructive apnea/hypopnea index (Kruskal-Wallis ANOVA 8.621, p = 0.0135) in the RSD group (median 0.7, IQR 0.3-0.9) than in the PLMS (median 1.7, IQR 0.7-3.5) or the non-RSD/non-PLMS (median 2.0, IQR 0.8-4.5) groups. Conclusions: There was an elevated frequency of RSD and elevated PLMS in our cohort of children born prematurely. Children born prematurely are at higher risk of iron deficiency which can be a contributor factor to sleep -related movement disorders. These results add new knowledge regarding the prevalence of RSD and PLMS in these children.